2021
DOI: 10.1111/zph.12837
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term surveillance for hepatitis E virus in an Italian two‐site farrow‐to‐finish swine farm

Abstract: In humans, hepatitis E virus (HEV) is responsible for an acute enterically transmitted hepatitis, which can become chronic in immune-compromised patients. Genotypes 3 and 4 (HEV-3 and HEV-4) are zoonotic, and domestic pigs and wild boar are the main reservoirs. The occurrence of autochthonous cases in Europe, which have been increasing over the last 10 years, has been associated with food-borne zoonotic transmission of HEV-3, mainly linked to consumption of undercooked or raw pork products (sausages containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…However, the use of pooled feces provided robust results as described in a previous study on HEV detection in pigs. The authors assessed pooled sample sensitivity in artificial pig fecal pools and reported a high sensitivity up to a fifty-fold dilution for positive fecal samples, allowing for the detection of the virus even if a pen contained 50 animals, 49 of which were negative at the moment of sampling [ 50 ]. In our study, pooling provides the advantage of reducing the number of samples to be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the use of pooled feces provided robust results as described in a previous study on HEV detection in pigs. The authors assessed pooled sample sensitivity in artificial pig fecal pools and reported a high sensitivity up to a fifty-fold dilution for positive fecal samples, allowing for the detection of the virus even if a pen contained 50 animals, 49 of which were negative at the moment of sampling [ 50 ]. In our study, pooling provides the advantage of reducing the number of samples to be analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…In wild reservoir confined in an area with no or limited contacts with farmed animals the variability of HEV-3 strains within the confined population is kept. This wild boar scenario is in sharp contrast to the situation on pig farms where the same HEV strain is identified repeatedly over the years, even after stamping out (Widen et al, 2011;Ianiro et al, 2021).…”
Section: Discussionmentioning
confidence: 76%
“…In wild reservoir confined in an area with no or limited contacts with farmed animals the variability of HEV‐3 strains within the confined population is kept. This wild boar scenario is in sharp contrast to the situation on pig farms where the same HEV strain is identified repeatedly over the years, even after stamping out (Ianiro et al., 2021; Widen et al., 2011).…”
Section: Discussionmentioning
confidence: 86%